2003
DOI: 10.1897/02-188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 4‐nonylphenol on phytoplankton and periphyton in aquatic microcosms

Abstract: The effects of nonylphenol (NP) on phytoplankton and periphyton were studied in 230 L outdoor microcosms. Phytoplankton cell density and biomass, phytoplankton and periphyton diversity, and assemblage composition were analyzed during a four-week preapplication period, followed by six weeks of NP treatment via controlled release and a six weeks postapplication period. Changes in species richness and diversity were not correlated with NP concentrations. However, changes in phytoplankton cell densities during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
1
24
1
Order By: Relevance
“…Nakai et al (2001) reported that M. aeruginosa growth was inhibited by plant-producing phenols with EC 50 values of 0.3-5.5 mg/L. Hense et al (2003) reported that S. subspicatus growth was inhibited by NPs with EC 50 values of 0.87-0.98 mg/L. The EC 50 values in these reports are close to our results.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Nakai et al (2001) reported that M. aeruginosa growth was inhibited by plant-producing phenols with EC 50 values of 0.3-5.5 mg/L. Hense et al (2003) reported that S. subspicatus growth was inhibited by NPs with EC 50 values of 0.87-0.98 mg/L. The EC 50 values in these reports are close to our results.…”
Section: Discussionsupporting
confidence: 89%
“…NPs are as high as 325 mg/L in surface water and reach 72 mg/kg in sediments Bennie, 1999;Gross-Sorokin et al, 2003;Kvestak and Ahel, 1994). Concerns about the toxicity and endocrine potential of NP have led to extensive studies on its fate in the environment and toxic effects on aquatic animals and plants over the last decade (Baldwin et al, 1997;Jobling et al, 1996;Schmude et al, 1999;Ho¨ss et al, 2002;Hense et al, 2003). However, studies about effects of NP on growth of M. aeruginosa and microcystin production are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers discovered that technical NPs were readily biodegradable in soils. Hense et al (2003) reported that the concentrations of NPs declined rapidly and reached the detection limit within 2 weeks in man-made aquatic microcosms. A removal of NPs by more than 90% in soil under normal field conditions within 1-3 months was observed by Marcomini, Capel, Lichtensteiger, Brunner, and Giger (1989).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the maximum concentration of NPs has been the 6300 lg/l detected in an effluent from a shipyard oil/water separator (Hale et al, 2000). Concerns about the toxicity and endocrine potential of NPs have led to extensive studies being carried out during the last decade on their fate in the environment and their toxic effects on aquatic animals and plants (Hense et al, 2003;Jobling, Sheahan, Osborne, Matthiessen, & Sumpter, 1996). However, the biochemical mechanisms of the effects of NPs on various biological functions have been poorly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…These systems can also be used to evaluate the impact on diversity and functioning of the intensity of the contamination (concentration and form of contaminants) and the exposure dynamics (duration, frequency), whilst simultaneously investigating the fate and the effects of pollutants (Belanger et al, 2000). These methods can also be used to identify the temporary, progressive or persistent effects of contaminants on communities (Rand et al, 2000;Belanger et al, 2002), by measuring their resilience, and also to distinguish between the direct and indirect ecological effects of disturbances caused by contaminants (Belanger et al, 2000;Culp et al, 2000;Hense et al, 2003). Just to provide recent examples of the variety of systems used, 3L liter Pyrex Erlenmeyer flasks have been used to study the response of microbial communities following exposure to glyphosate (Pesce et al, 2009a), indoor experimental channels have been used to study the combined effect of physical factors and exposure to diuron on benthic microbial communities (Villeneuve, 2008), and artificial outdoor mesocosms (surface area 25 m 2 ) have been used by Vera et al (2010) to evaluate the impact of Roundup on periphyton communities.…”
Section: Microcosms Mesocosms and Macrocosmsmentioning
confidence: 99%